The Economic of Mini Purse Seine Fisheries by Season and Fishing Ground in Kei Island - Simon Marsholl Picaulima; Eko Sri Wiyono; Meyske Angel Rahantoknam; Julianus Notanubun (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
The economic profit of mini purse seine fishing business in the coastal area of the Kei Islands is different in every season and fishing ground. The aim.of.this analyze the profit of the mini purse seine fishing business on every season and on fishing grounds. Collecting data using survey methods, determining respondents using purposive sampling. Data were analyzed using fishing ground analysis and economic analysis. The results of.the identification indicate that during the transitional season 1 and west, the mini purse seine fishing ground are located on the eastern coast of Tayando and eastern Kei Besar coast and the Nerong strait. The result of the identification shows that the fishing grounds of mini purse seine in the western and transitional 1 seasons in the waters of the eastern Tayando Island, the Nerong Strait, and the waters of the eastern Kei Besar Island, while at the beginning of.the east monsoon in the waters of.the eastern part of Tayando Island and the Nerong Strait.The.results.of.the.economic.analysis.show.that the fishing grounds waters of.the eastern Tayando Islandhaves higher economic profit in each season because it has low efficiency, effectiveness, productivity, and high business profit. Fisheries managers in Maluku Province need to work together with fishermen to regulate production inputs in the fishing grounds of the Nerong Strait every season.